Me Too as Transnational Advocacy Networks: The Case of Anti-Sexual Violence Movement in Indonesia - Dewi, Karina Utami; Fathana, Hangga; Rohma, Masitoh Nur (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
The research discusses the anti-sexual movement in Indonesia as a part of the global movement of Me Too and transnational advocacy networks. It aims to answer how the transnational advocacy movement explains the movement against sexual violence in Indonesia. The argument of the research is offered in three parts. First, it argues that the anti-sexual violence movement in Indonesia is a part of transnational advocacy networks. The analysis is provided by explaining the process of boomerang patterns, political entrepreneurs, and international contacts. Second, as part of a transnational advocacy network, the anti-sexual violence movement in Indonesia uses four tactics: information politics, symbolic politics, leverage politics, and accountability politics. The research argues that the anti-sexual violence movement uses all four of the tactics to achieve its goals. Lastly, the third part of the argument discusses the five stages of transnational advocacy networks that the movement has achieved with regard to their goals, and the research argues that it has reached all the stages except for the last one, which is influenced by state behavior.